Transthyretin deposition in the eye in the era of effective therapy for hereditary ATTRV30M amyloidosis. (2nd January 2019) - Buxbaum, Joel N.; Brannagan, Thomas; Buades-Reinés, Juan; Cisneros, Eugenia; Conceicao, Isabel; Kyriakides, Theodoros; Merlini, Giampaolo; Obici, Laura; Plante-Bordeneuve, Violaine; Rousseau, Antoine; Sekijima, Yoshiki; Imai, Akira; et al.
Abstract: Background: Ocular abnormalities have been known to occur in hereditary amyloidotic polyneuropathy since the 1950s. While vitreous opacities and scalloped pupils were described early it has become evident that every component of the eye from the conjunctiva to the retinal vasculature can be involved. Reports from the major centres in Japan, Portugal and Sweden, which primarily treat patients with ATTRV30M, have indicated that with the increased longevity seen in patients treated with liver transplantation the frequency of the more severe eye findings, notably vitreous opacities and subsequent glaucoma, are being detected more frequently. Methods: In an attempt to confirm that the experience was similar in a broader range of locales we performed a survey of ten treatment centres in eight countries to determine the frequency of severe ocular abnormalities (vitreous opacities and glaucoma) in 804 patients with V30M disease and whether there was any relationship to treatment with liver transplantation or the transthyretin stabilizer tafamidis. Results: The data indicate that the frequency of these abnormalities increases with increasing duration of disease. In patients broadly matched for duration of disease the frequency was higher in subjects who had undergone liver transplantation than in those who were untreated. Conclusions: Retrospective surveys are subject to a number of potential biases. In this case, the major potential confounders were defining the time of disease onset and physician bias in choice of therapy, particularly regarding the choice of patients and the time in their course when they should undergo liver transplantation, and when and whether they should receive tafamidis. Nonetheless it appears that the incidence of severe ocular abnormalities in V30M subjects from centres around the world is similar to those found in centres in the areas endemic for this variant protein. The incidence increased with duration of disease regardless of therapy with the highest frequencies seen in patients more than ten years after diagnosis who had undergone liver transplantation.